Patient Satisfaction and Health-Related Quality of Life After Cardiac Catheterization: A Predictive Model - Lely Puspita Candra Dewi; Ferdi Antonio; Dewi Sri Surya Wuisan (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Coronary heart disease, a leading global cause of death, including in Indonesia, is managed through promotive, preventive, and curative approaches, with cardiac catheterization evolving as a common non-surgical intervention method in Indonesian hospitals, aiming to improve patient’s quality of life and outcomes. This study examines the factors affecting patient satisfaction following cardiac catheterization and their impact on health-related quality of life (HRQoL). Data was collected from 154 respondents at three private hospitals in Surabaya, Indonesia, through online questionnaires and analyzed using Partial Least-Structural Equation Modeling (PLS-SEM). This study found that treatment outcome, physician-patient communication, attentive care, organization of care, and servicescape significantly influence patient satisfaction (p-value <0.05; CI 95%). In turn, patient satisfaction positively impacts HRQoL (p=0.000, β=0.848). The results indicate that the model has moderate explanatory power and strong predictive relevance in estimating patient satisfaction following cardiac catheterization. This study benefited hospital administration in improving patient satisfaction with catheterization services.